2020
DOI: 10.1007/s12015-020-09953-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel Evidence that Purinergic Signaling - Nlrp3 Inflammasome Axis Regulates Circadian Rhythm of Hematopoietic Stem/Progenitor Cells Circulation in Peripheral Blood

Abstract: We found that circadian changes in ATP level in peripheral blood (PB) activate the Nlrp3 inflammasome, which triggers diurnal release of hematopoietic stem/progenitor cells (HSPCs) from murine bone marrow (BM) into PB. Consistent with this finding, we observed circadian changes in expression of mRNA for Nlrp3 inflammasome-related genes, including Nlrp3, caspase 1, IL-1β, IL-18, gasdermin (GSDMD), HMGB1, and S100A9. Circadian release of HSPCs from BM into PB as well as expression of Nlrp3-associated genes was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The researchers first illustrated that the MBL-initiated ComC and coagulation cascade (CoaC) are involved in triggering the mobilization of HSPCs [ 95 ]. ATP is released extracellularly primarily through the pannexin-1 channel and activates the MBL-ComC (CoaC) pathway as a DAMP via purinergic receptors [ 95 , 96 , 97 ]. The researchers then proposed that the ATP-induced NLRP3 inflammasome acts as a neutralizer that connects purinergic signaling with the activation of the ComC, which is required for the egress of HSPCs from the BM into the PB [ 98 ].…”
Section: Extracellular Signals Activate the Inflammasome Through Pmentioning
confidence: 99%
“…The researchers first illustrated that the MBL-initiated ComC and coagulation cascade (CoaC) are involved in triggering the mobilization of HSPCs [ 95 ]. ATP is released extracellularly primarily through the pannexin-1 channel and activates the MBL-ComC (CoaC) pathway as a DAMP via purinergic receptors [ 95 , 96 , 97 ]. The researchers then proposed that the ATP-induced NLRP3 inflammasome acts as a neutralizer that connects purinergic signaling with the activation of the ComC, which is required for the egress of HSPCs from the BM into the PB [ 98 ].…”
Section: Extracellular Signals Activate the Inflammasome Through Pmentioning
confidence: 99%
“…Immunosurveillance is maintained by the constant flow of hematopoietic stem cells (HPSCs) from the bone marrow and recirculation in the blood and lymph via a bioactive phosphoshingolipid, Spingosine-1 phosphate (S1P), which acts as a chemoattractant of HPSCs (Massberg et al, 2007 ). The number of HPSCs has been shown to be highly circadian, with the majority of HPSCs circulating in peripheral blood in the early morning hours (Golan et al, 2018 ; Adamiak et al, 2020 ; Ratajczak et al, 2020 ). Both S1P levels and the activated C5 complement pathway are reportedly circadian and play a role in the diurnal chemotaxis of HPSC egression of stem cells from bone marrow to the peripheral blood circulation to maintain immunosurveillance.…”
Section: Co-regulatory Roles Of Complement and Sleep On Immunosurveilmentioning
confidence: 99%
“…In addition, other mechanisms of AIM2 transcriptional regulation may exist. For example, it was shown that the mRNA expression of most inflammasomes, including AIM2, is affected by the circadian rhythm in mice, showing higher levels in peripheral blood granulocytes during the morning hours and decreasing gradually through the late evening hours [ 24 ].…”
Section: Brief Overview Of Aim2 Inflammasome Activation and Regulamentioning
confidence: 99%